Improving Student's Vocabulary Mastery Through Hello English Application at Tenth-Grade Students of High School - Ulfa Ulfa; Wiyaka Wiyaka; Sri Wahyuni (Lingua Franca, 2023)
This study aims to determine 1) the effect of using the Hello English application in English teaching on improving students' ability in vocabulary mastery and 2) determine students' perceptions of the application of Hello English application in teaching English subjects at SMAN 1 Mayong, Jepara. This study used a type of quantitative research with a pseudo-experimental research design. This study used test data collection techniques and questionnaires to measure students' vocabulary mastery. The population of this study was grade X students of SMAN 1 Mayong, with a total of 72 students consisting of grades X 7 and X 9. The test result data in this study was calculated and analyzed automatically using SPSS. Based on the data analysis using the t-test, the test data shows that the result of t count (df = 70) = 9.881 and p-value or significant level of 0.000, which is smaller than 0.05. Researchers use α = 0.05 (5%) as a significant standard, so the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted because the p or sig (2-tailed) value of 0.000 is lower than α = 0.05 (5%). This means a significant difference exists between the results of using the Hello English Application in teaching vocabulary to grade X students of SMA Negeri 1 Mayong for the 2022/2023 school year. The results showed that the Hello English application significantly increased students' vocabulary mastery after treatment. The average score of experimental class students increased from 73 on the pre-test to 91 on the post-test.Moreover, the control class's average score was 74 on the pre-test to 79 on the post-test. This means that the average score of the students in the experimental class is higher than the average score in the control class. Researchers concluded that the Hello English Application is effective through mastery of student vocabulary, especially for tenth-grade students of SMA Negeri 1 Mayong for the 2022/2023 academic year. Based on the questionnaire, the results showed that using the Hello English application in teaching English has many positive impacts on students, including students being more motivated in learning and making it easier for students to understand the material.